Treatment of metastatic malignant melanoma during pregnancy with a BRAF kinase inhibitor: A case report - Megan Pagan; Heather Jinks; Mark Sewell (Elsevier, 2019)
Background: Melanoma accounts for 8% of all malignancies encountered during pregnancy. BRAF kinase inhibitors have shown promise in the treatment of late-stage melanoma; however, there have been no studies and only one previous case report regarding its use in pregnancy. Case: A 25-year-old woman, gravida 1, at 20 weeks of gestation presented to the clinic with a complaint of a lump on her neck and dyspnea. She had had a melanoma that was surgically treated 5 years prior to her pregnancy. A biopsy was performed and she was found to have metastatic melanoma. After multidisciplinary discussion, the patient was offered treatment with vemurafenib, a BRAF kinase inhibitor, and the mass reduced in size. Conclusion: Malignancy during pregnancy poses both medical and ethical dilemmas in the management and treatment of cancer. The treatment of late-stage melanoma in pregnancy with a BRAF kinase inhibitor may be an option. Keywords: Melanoma, Pregnancy, BRAF inhibitor